Anion exchange membrane with high hydroxyl conductivity and preparation method thereof
By pretreating and interfacial polymerization of the anion exchange membrane base film, a high-density separation layer is formed, which solves the problem of low hydroxide conductivity of the anion exchange membrane and significantly improves its conductivity and application potential.
Patent Information
- Application Number
- CN202411913492.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The ionic conductivity of anion exchange membrane is relatively low, especially the conductivity to hydroxide ions, which limits its application in the fields of electrolysis and other water.
By pretreating the base film of the ion exchange membrane and performing interfacial polymerization in the aqueous phase and organic phase solution, a polymethylene separation layer with high density and chemical stability is formed to improve the hydroxide conductivity of the anion exchange membrane.
The hydroxide conductivity of the anion exchange membrane has been significantly improved and its application potential in the fields of electrolyzing water.
Smart Images

Figure CN119701670A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange membrane materials, and in particular to an anion exchange membrane with high hydroxide conductivity and a preparation method thereof. Background Art
[0002] Anion exchange membrane is a special membrane material used to separate and transfer anions in solution. This type of membrane is usually composed of polymers with positively charged groups that can attract and conduct anions while blocking the passage of cations. It is widely used in water electrolysis, fuel cells, electrodialysis, water treatment and other fields.
[0003] As the most advanced water electrolysis technology, the development history of anion exchange membrane water electrolysis system is relatively short, and the research on high-performance anion exchange membrane is still in the early stage of exploration. Compared with the mature proton exchange membrane, the ion conductivity and chemical stability of anion exchange membrane are lower than those of perfluorosulfonic acid membrane. In terms of conductivity, compared with proton exchange membrane, the ion conductivity of anion exchange membrane for OH- is lower, which is about half of the conductivity of proton exchange membrane for H+. The relatively low ion conductivity of anion exchange membrane has always been the main obstacle to the large-scale promotion of anion exchange membrane water electrolysis system. It is of great research significance to provide a simple method for preparing anion exchange membrane with high hydroxide conductivity. Summary of the invention
[0004] The object of the present invention is to provide an anion exchange membrane with high hydroxide conductivity and a preparation method thereof, so as to solve the problem that the ion conductivity of the anion exchange membrane is relatively low.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing an anion exchange membrane with high hydroxide conductivity, comprising the following steps: pre-treating an ion exchange membrane base film to obtain a pre-treated ion exchange membrane base film; adding 3,3'-diaminobenzidine to a mixed solution of deionized water and anhydrous ethanol to obtain an aqueous phase solution; adding terephthalaldehyde to a mixed solution of n-hexane and ethyl acetate to obtain an organic phase solution; immersing the pre-treated ion exchange membrane base film in the aqueous phase solution, then taking out the immersed base film, removing the surface solution with a rubber roller, and then immersing it in the organic phase solution to perform an interfacial polymerization reaction to obtain a base film after an interfacial polymerization reaction; sequentially drying and curing the base film after the interfacial polymerization reaction; and performing an alkali-doping treatment on the cured base film to obtain an anion exchange membrane.
[0007] According to one embodiment of the present invention, the material of the anion exchange membrane base film is polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polyphenylene sulfide. The present invention also provides a combination of one or more of the above.
[0008] According to one embodiment of the present invention, the pretreatment comprises: immersing the ion exchange membrane base film in deionized water at 20° C.-30° C. for 48 h-72 h, and replacing the deionized water every 24 h.
[0009] According to one embodiment of the present invention, the concentration of 3,3'-diaminobenzidine in the aqueous solution is 0.05wt%-2.00wt%, and the mass ratio of deionized water to anhydrous ethanol in the aqueous solution is 2:1.
[0010] According to one embodiment of the present invention, the concentration of terephthalaldehyde in the organic phase solution is 0.10wt%-3.00wt%, and the mass ratio of n-hexane to ethyl acetate in the organic phase solution is 2:1.
[0011] According to one embodiment of the present invention, the pretreated ion exchange membrane base film is immersed in the aqueous solution for 10 min to 60 min, and the interfacial polymerization reaction lasts for 3 min to 10 min.
[0012] According to one embodiment of the present invention, in the step of sequentially drying and curing the base film after the interfacial polymerization reaction, the curing time is 0.5 min-2.5 min, and the curing temperature is 50-80°C.
[0013] According to one embodiment of the present invention, in the step of subjecting the cured base film to alkali treatment, the alkali treatment is to immerse the cured base film in a 3 mol / L KOH solution for 4 h to 12 h.
[0014] The present invention provides an anion exchange membrane prepared by the above preparation method.
[0015] The invention provides an anion exchange membrane with high hydroxide conductivity and a preparation method thereof. A pretreated ion exchange membrane base membrane, an aqueous phase solution containing 3,3'-diaminobenzidine, and an organic phase solution containing terephthalaldehyde are prepared respectively. The pretreated ion exchange membrane base membrane is immersed in the aqueous phase solution so that the ion exchange membrane base membrane fully absorbs 3,3'-diaminobenzidine. The immersed base membrane is taken out and the surface solution is removed by a rubber roller so that the subsequent interfacial polymerization reaction is more uniform. The base membrane is immersed in the organic phase solution for interfacial polymerization reaction so that the 3,3'-diaminobenzidine adsorbed on the surface of the ion exchange membrane base membrane is fully in contact with the terephthalaldehyde in the organic phase solution and a polymerization reaction occurs at the interface between the two phases. A separation layer is formed on the ion exchange membrane base membrane. The membrane is dried and solidified so that the formed separation layer is further cross-linked to improve its compactness and stability. The base membrane is then treated with alkali to obtain an anion exchange membrane with high hydroxide conductivity. The present invention utilizes the nucleophilic substitution reaction between aldehyde groups and diamino groups to generate aromatic polyazomethine with good chemical stability and high mechanical strength, and adopts room temperature interfacial polymerization to prepare a composite membrane of an ultra-thin polyazomethine separation layer. The ion transmission channel of the dense polyazomethine separation layer is regulated by changing the molecular configuration of aldehyde and amine monomers, and the thickness of the dense polyazomethine separation layer is regulated by regulating the interfacial polymerization reaction conditions, thereby significantly shortening the ion transmission path and improving the ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 Shown is a flow chart of a method for preparing an anion exchange membrane with high hydroxide conductivity provided by one embodiment of the present disclosure. DETAILED DESCRIPTION
[0018] like Figure 1 As shown, the present invention provides a method for preparing an anion exchange membrane with high hydroxide conductivity, comprising the following steps:
[0019] S1, pre-treating the ion exchange membrane basement membrane to obtain a pre-treated ion exchange membrane basement membrane;
[0020] S2, adding 3,3'-diaminobenzidine to a mixture of deionized water and anhydrous ethanol to obtain an aqueous solution;
[0021] S3, adding terephthalaldehyde to a mixture of n-hexane and ethyl acetate to obtain an organic phase solution;
[0022] S4, immersing the pretreated ion exchange membrane base film into an aqueous solution, then taking out the immersed base film and removing the surface solution with a rubber roller, and then immersing it into an organic solution for interfacial polymerization to obtain a base film after interfacial polymerization;
[0023] S5, sequentially drying and curing the base film after the interfacial polymerization reaction;
[0024] S6. The cured base film is treated with alkali to obtain an anion exchange membrane.
[0025] In the examples of the present invention, unless otherwise specified, the raw materials used are conventional commercially available products in the art.
[0026] The present invention pre-treats the ion exchange membrane base film to obtain the pre-treated ion exchange membrane base film.
[0027] In the embodiment of the present invention, the material of the ion exchange membrane base film can be one or any combination of two or more of polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, and polyphenylene sulfide.
[0028] In the embodiment of the present invention, the membrane cut-off molecular weight of the ion exchange membrane base membrane may be 50 KDa-150 KDa, more preferably 100 KDa.
[0029] In the embodiment of the present invention, the pretreatment preferably comprises: immersing the ion exchange membrane base film in deionized water at 20° C.-30° C. for 48 h-72 h, and replacing the deionized water every 24 h.
[0030] The present invention adds 3,3'-diaminobenzidine into a mixed solution of deionized water and anhydrous ethanol to obtain an aqueous phase solution, wherein the mass ratio of deionized water to anhydrous ethanol in the aqueous phase solution is 2:1.
[0031] In an embodiment of the present invention, the concentration of 3,3'-diaminobenzidine in the aqueous solution may be 0.05wt%-2.00wt%, for example, 0.10wt%-1.00wt%. The present invention controls the concentration of 3,3'-diaminobenzidine in the aqueous solution within the above range so that the adsorption amount of 3,3'-diaminobenzidine by the ion exchange membrane base film is at the optimal reaction amount.
[0032] The invention adds terephthalaldehyde into a mixed solution of n-hexane and ethyl acetate to obtain an organic phase solution, wherein the mass ratio of n-hexane to ethyl acetate in the organic phase solution is 2:1.
[0033] In the embodiment of the present invention, the concentration of terephthalaldehyde in the organic phase solution can be 0.10wt%-3.00wt%, for example, 0.25wt%-2.00wt%. The present invention controls the concentration of terephthalaldehyde in the organic phase solution within the above range to ensure that the interfacial polymerization reaction is at the optimal reaction level.
[0034] In the embodiment of the present invention, there is no particular order in which the ion exchange membrane base film, aqueous phase solution and organic phase solution pretreated by the above technical solution are prepared.
[0035] After obtaining the pretreated ion exchange membrane base membrane, aqueous solution and organic solution, the present invention immerses the pretreated ion exchange membrane base membrane into the aqueous solution, then takes out the immersed base membrane, removes the surface solution with a rubber roller, and then immerses it into the organic solution for interfacial polymerization reaction to obtain the base membrane after the interfacial polymerization reaction.
[0036] In an embodiment of the present invention, the time for the pretreated ion exchange membrane base film to be immersed in the aqueous solution can be 10 min-60 min, for example, 15 min-45 min. The present invention controls the time for the pretreated ion exchange membrane base film to be immersed in the aqueous solution within the above range, so that the 3,3'-diaminobenzidine in the aqueous solution is fully adsorbed onto the surface of the pretreated ion exchange membrane base film.
[0037] In an embodiment of the present invention, the time of the interfacial polymerization reaction can be 3 min-10 min, for example, 4 min-8 min. The present invention controls the time of the interfacial polymerization reaction within the above range to allow the 3,3'-diaminobenzidine adsorbed on the surface of the pretreated ion exchange membrane substrate to fully react with the terephthalaldehyde in the organic phase solution.
[0038] After obtaining the base film after the interfacial polymerization reaction, the present invention sequentially dries and solidifies the base film after the interfacial polymerization reaction.
[0039] In an embodiment of the present invention, the curing time may be 0.5 min-2.5 min, for example, 1 min-2 min. In an embodiment of the present invention, the curing temperature may be 50° C.-80° C. The present invention controls the curing temperature and time within the above range to make the ion exchange membrane separation layer in an optimal cross-linked state.
[0040] After obtaining the heat-cured base film, the present invention performs an alkali-doping treatment on the cured base film, that is, immersing the base film in a 3 mol / L KOH solution.
[0041] In the embodiment of the present invention, the alkali doping treatment time can be 4h-12h, for example, 6h-10h. The present invention controls the alkali doping time within the above range so that the ion exchange membrane can fully absorb the alkali solution, construct ion transmission channels, and facilitate ion conduction.
[0042] The method for preparing an anion exchange membrane with high hydroxide conductivity provided by the invention has the advantages of simple operation, mild reaction conditions and suitability for large-scale production.
[0043] The present invention also provides an anion exchange membrane with high hydroxide conductivity prepared by the preparation method of the above technical solution.
[0044] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] A method for preparing an anion exchange membrane with high hydroxide conductivity (the following steps without temperature indication are all carried out at room temperature) comprises the following steps:
[0047] (1) A polyethersulfone (PES) ion exchange membrane substrate (with a molecular weight cutoff of 100 KDa) with a size of 2 cm×2 cm was soaked in deionized water for pretreatment. The soaking time was 48 hours, and the deionized water needed to be replaced every 24 hours.
[0048] (2) 0.2 g of 3,3'-diaminobenzidine was mixed with 133.20 g of deionized water and 66.60 g of anhydrous ethanol to prepare an aqueous solution having a concentration of 0.1 wt % of 3,3'-diaminobenzidine.
[0049] (3) 1 g of terephthalaldehyde was mixed with 132.67 g of n-hexane and 66.33 g of ethyl acetate to prepare an organic phase solution with a terephthalaldehyde concentration of 0.5 wt %.
[0050] (4) The pretreated ion exchange membrane base membrane obtained in step (1) is immersed in the aqueous solution obtained in step (2) for 45 minutes, and then the immersed base membrane is taken out and the surface solution is removed with a rubber roller, and then immersed in the organic phase solution for interfacial polymerization reaction for 8 minutes to obtain a base membrane after the interfacial polymerization reaction.
[0051] (5) After drying the base film obtained after the interfacial polymerization reaction in step (4), the base film is placed in a constant temperature drying oven at 80° C. for curing for 1 minute to obtain a cured base film.
[0052] (6) The cured base membrane obtained in step (5) is immersed in a 3 mol / L KOH solution for 10 hours to obtain an anion exchange membrane with high hydroxide conductivity.
[0053] The anion exchange membrane with high hydroxide conductivity prepared in Example 1 was stored in a sealed bag for subsequent measurement. A 1 mol / L KOH solution was selected as the electrolyte solution, and the membrane was analyzed by AC impedance spectroscopy using an electrochemical workstation, and the hydroxide conductivity of the membrane was obtained by measuring the membrane thickness.
[0054] The test results show that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 1 is 37.02 mS / cm.
[0055] Example 2
[0056] An anion exchange membrane with high hydroxide conductivity was prepared according to the method of Example 1, except that in step (2), 0.5 g of 3,3'-diaminobenzidine was mixed with 133.00 g of deionized water and 66.50 g of anhydrous ethanol to prepare an aqueous solution with a concentration of 0.25 wt% of 3,3'-diaminobenzidine.
[0057] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Example 2 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 2 was 39.85 mS / cm.
[0058] Example 3
[0059] An anion exchange membrane with high hydroxide conductivity was prepared according to the method of Example 1, except that in step (2), 1 g of 3,3'-diaminobenzidine was mixed with 132.67 g of deionized water and 66.33 g of anhydrous ethanol to prepare an aqueous solution with a concentration of 0.5 wt% of 3,3'-diaminobenzidine.
[0060] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Example 3 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 3 was 43.14 mS / cm.
[0061] Example 4
[0062] An anion exchange membrane with high hydroxide conductivity was prepared according to the method of Example 1, except that in step (2), 1.5 g of 3,3'-diaminobenzidine was mixed with 132.33 g of deionized water and 66.17 g of anhydrous ethanol to prepare an aqueous solution with a concentration of 0.75 wt% of 3,3'-diaminobenzidine.
[0063] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Example 4 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 4 was 41.78 mS / cm.
[0064] Example 5
[0065] An anion exchange membrane with high hydroxide conductivity was prepared according to the method of Example 1, except that in step (2), 2 g of 3,3'-diaminobenzidine was mixed with 132.00 g of deionized water and 66.00 g of anhydrous ethanol to prepare an aqueous solution with a concentration of 1.00 wt% of 3,3'-diaminobenzidine.
[0066] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Example 5 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 5 was 41.05 mS / cm.
[0067] Example 6
[0068] An anion exchange membrane with high hydroxide conductivity was prepared according to the method of Example 1, except that: Step (2) was to mix 1 g of 3,3'-diaminobenzidine with 132.67 g of deionized water and 66.33 g of anhydrous ethanol to prepare an aqueous phase solution with a 3,3'-diaminobenzidine concentration of 0.5 wt %. Step (3) was to mix 2 g of terephthalaldehyde with 132.00 g of n-hexane and 66.00 g of ethyl acetate to prepare an organic phase solution with a terephthalaldehyde concentration of 1.00 wt %.
[0069] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Example 6 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 6 was 47.69 mS / cm.
[0070] Comparative Example 1
[0071] An anion exchange membrane was prepared according to the method of Example 1, except that in step (3), 1 g of o-phthalaldehyde was mixed with 132.67 g of n-hexane and 66.33 g of ethyl acetate to prepare an organic phase solution with an o-phthalaldehyde concentration of 0.5 wt%.
[0072] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 1 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 1 was 12.56 mS / cm.
[0073] Comparative Example 2
[0074] An anion exchange membrane was prepared according to the method of Example 1, except that in step (3), 1 g of isophthalaldehyde was mixed with 132.67 g of n-hexane and 66.33 g of ethyl acetate to prepare an organic phase solution with an isophthalaldehyde concentration of 0.5 wt %.
[0075] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 2 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 2 was 28.45 mS / cm.
[0076] Comparative Example 3
[0077] An anion exchange membrane was prepared according to the method of Example 1, except that the time of the interfacial polymerization reaction in step (4) was 4 minutes.
[0078] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 3 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 3 was 33.67 mS / cm.
[0079] Comparative Example 4
[0080] An anion exchange membrane was prepared according to the method of Example 1, except that in step (5), after the base membrane was dried, it was placed in a constant temperature drying oven at 50° C. for curing for 1 min.
[0081] The performance of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 4 was tested in the same manner as in Example 1. The test results showed that the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Comparative Example 4 was 35.67 mS / cm.
[0082] In summary, the hydroxide conductivity of the anion exchange membrane with high hydroxide conductivity prepared in Example 6 of the present invention is 47.69 mS / cm, which is significantly higher than that of the comparative example.
[0083] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0084] The phrases "one embodiment", "an embodiment", etc. mentioned in the specification indicate that the embodiment described may include a specific feature, structure or characteristic, but not every embodiment may include the specific feature, structure or characteristic. In addition, such phrases do not necessarily refer to the same embodiment. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it is within the knowledge of those skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments, whether explicitly or not explicitly described.
[0085] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0086] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A method for preparing an anion exchange membrane with high hydroxide conductivity, comprising the following steps: pre-treating the ion exchange membrane base membrane to obtain a pre-treated ion exchange membrane base membrane; adding 3,3'-diaminobenzidine to a mixture of deionized water and anhydrous ethanol to obtain an aqueous phase solution; Adding terephthalaldehyde to a mixture of n-hexane and ethyl acetate to obtain an organic phase solution; Immersing the pretreated ion exchange membrane base film into the aqueous solution, then taking out the immersed base film and removing the surface solution with a rubber roller, and then immersing it into the organic solution to perform an interfacial polymerization reaction, thereby obtaining a base film after the interfacial polymerization reaction; The base film after the interfacial polymerization reaction is sequentially dried and cured; The cured base film is treated with alkali to obtain an anion exchange membrane.
2. The preparation method according to claim 1, characterized in that: The material of the anion exchange membrane base film is one or a combination of two or more of polyethersulfone, polyacrylonitrile, polyvinylidene fluoride and polyphenylene sulfide.
3. The preparation method according to claim 1, characterized in that: The pretreatment comprises: immersing the ion exchange membrane base film in deionized water at 20° C.-30° C. for 48 h-72 h, and replacing the deionized water every 24 h.
4. The preparation method according to claim 1, characterized in that: The concentration of 3,3'-diaminobenzidine in the aqueous phase solution is 0.05wt%-2.00wt%, and the mass ratio of deionized water to anhydrous ethanol in the aqueous phase solution is 2:
1.
5. The preparation method according to claim 1, characterized in that: The concentration of terephthalaldehyde in the organic phase solution is 0.10wt%-3.00wt%, and the mass ratio of n-hexane to ethyl acetate in the organic phase solution is 2:
1.
6. The preparation method according to claim 1, characterized in that: The pretreated ion exchange membrane base film is immersed in the aqueous solution for 10 min to 60 min, and the interfacial polymerization reaction lasts for 3 min to 10 min.
7. The preparation method according to claim 1, characterized in that: In the steps of sequentially drying and curing the base film after the interfacial polymerization reaction, the curing time is 0.5 min-2.5 min, and the curing temperature is 50-80°C.
8. The preparation method according to claim 1, characterized in that: In the step of subjecting the cured base film to alkali treatment, the alkali treatment is to immerse the cured base film in a 3 mol / L KOH solution for 4 hours to 12 hours.
9. An anion exchange membrane prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation and application of ionic membrane material with nano / sub-nano pore channels
CN113234326A
Polyarylene ion exchange membrane and preparation method thereof
CN117866264A
Polybenzimidazole polymer electrolyte membrane with main chain containing Schiff base and preparation method of polybenzimidazole polymer electrolyte membrane
CN118580493A
Method for Making High Performance Mixed Matrix Membranes
US20090149565A1
Molecularly porous cross-linked membranes
US20230330604A1